β2-integrins control HIF1α activation in human neutrophils - Kling, Lovis; Eulenberg-Gustavus, Claudia; Jerke, Uwe; Rousselle, Anthony; Eckardt, Kai-Uwe; Schreiber, Adrian; Kettritz, Ralph (Frontiers in Immunology, 2024)
During inflammation, human neutrophils engage b2-integrins to migrate from the blood circulation to inflammatory sites with high cytokine but low oxygen concentrations. We tested the hypothesis that inhibition of prolyl hydroxylase domain-containing enzymes (PHD), cytokines, and b2-integrins cooperate in HIF pathway activation in neutrophils. Using either the PHD inhibitor roxadustat (ROX) (pseudohypoxia) or normobaric hypoxia to stabilize HIF, we observed HIF1a protein accumulation in adherent neutrophils. Several inflammatory mediators did not induce HIF1a protein but provided additive or even synergistic signals (e.g. GM-CSF) under pseudohypoxic and hypoxic conditions. Importantly, and in contrast to adherent neutrophils, HIF1a protein expression was not detected in strictly suspended neutrophils despite PHD enzyme inhibition and the presence of inflammatory mediators. Blocking b2-integrins in adherent and activating b2-integrins in suspension neutrophils established the indispensability of b2-integrins for increasing HIF1a protein. Using GM-CSF as an example, enhanced HIF1a mRNA transcription via JAK2/STAT3 was necessary but not sufficient for HIF1a protein upregulation. Importantly, we found that b2-integrins led to HIF1a mRNA translation by phosphorylation of the essential translation initiation factors eIF4E and 4EBP1. Finally, pseudohypoxic and hypoxic conditions inducing HIF1a consistently delayed apoptosis in adherent neutrophils on fibronectin under low serum concentrations. Pharmacological HIF1a inhibition reversed delayed apoptosis, supporting the importance of this pathway for neutrophil survival under conditions mimicking extravascular sites. We describe a novel, b2-integrin controlled mechanism of HIF1a stabilization in human neutrophils. Conceivably, this mechanism restricts HIF1a activation in response to hypoxia and pharmacological PHD enzyme inhibitors to neutrophils migrating towards inflammatory sites.